The relative paleointesnity and Dole effect in the north of the South China Sea - Xiaoqiang Yang; Zhihua Su; Gangjian Wei; Tingwei Zhang; Qiong Chen (PANGAEA, 2024)
This dataset is including the relative paeleointensity (RPI), oxygen isotope, sea surface temperature and Dole effect data over the past ~150 kyr derived from thress cores PC27, PC83 and PC111, which located on the norht of South China Sea. These data were used to discuss the possilbe links of geomagnetic field variations with hydrological cycles in the South China Sea since the Late Pleistocene. The RPI was reconstructed using NRM/SIRM ratio for the independent cores, and then stacked the synthesized curve SPIS-150. The oxygen isotope and SST were measured using planktonic foraminifer, and the Dole effect was calculated based on them.The age of the cores was reconstructed by tuning our delta18O data to the delta18O curves of the PISO-1500 stack (Channell et al., 2009; doi:10.1016/j.epsl.2009.03.012), SCS-Stack (Wang et al., 2016; doi:10.1016/j.quascirev.2016.04.009) and ODP Site 1144 (Bühring et al., 2004; doi:10.2973/odp.proc.sr.184.205.2004), and by referencing the relative intensity (RPI) of cores to the global master curve PISO-1500 (Channell et al., 2009; doi:10.1016/j.epsl.2009.03.01).